Н. С. Трубецкой: биография и научные взгляды - Клейнер, Ю. А. (Kalbotyra, 1985)
The paper is a review of “N.S. Trubelzkoy’s Letters and Notes” by R. Jakobson – a book comprising 196 letters, sent mainly to R. Jakobson and others during the period of 1920–1938, and also several articles.